Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Associations of Blood and Urinary Heavy Metals with Stress Urinary Incontinence Risk Among Adults in NHANES, 2003–2018 - Maoling Fu; Zifan Zhu; Yechen Xiang; Qiaoyue Yang; Quan Yuan; Xinyu Li; Genzhen Yu (Biological Trace Element Research, 2025)
People come into contact with heavy metals in various ways in their daily lives. Accumulating evidence shows that toxic metal exposure is hazardous to human health. However, limited information is available regarding the impact of metal mixtures on stress urinary incontinence (SUI). Therefore, we used data from 10,622 adults from the 2003–2018 National Health and Nutrition Examination Survey (NHANES) to investigate the independent and comprehensive association between heavy metal co-exposure and SUI. Among them, 2455 (23.1%) had been diagnosed with SUI, while the rest had no SUI. We evaluated the independent and combined associations of 3 blood metals and 10 urinary metals with SUI risk, along with subgroup analyses according to age and gender. In the single-exposure model, blood cadmium (Cd), lead (Pb), mercury (Hg), urinary Cd, Pb, and cesium (Cs) were found to be positively connected with SUI risk. Moreover, weighted quantile sum (WQS) regression, quantile-based g-computation (qgcomp), and Bayesian kernel machine regression (BKMR) consistently demonstrated blood and urinary metal–mixed exposure were positively associated with the risk of SUI, and emphasized that blood Pb and Cd and urinary Cd and Cs were the main positive drivers, respectively. This association was more pronounced in the young and middle-aged group (20–59 years old) and the female group. Nevertheless, further research is necessary to validate these significant findings.

The association of mixed multi-metal exposure with sleep duration and self-reported sleep disorder: A subgroup analysis from the National Health and Nutrition Examination Survey (NHANES) - Zifan Zhu; Yongjun Wang; Yuanlong Wang; Maoling Fu; Xinxin Luo; Guojun Wang; Jian Zhang; Xiujuan Yang; Wei Shan; Cunxue Li; Tiebang Liu (Environmental Pollution, 2024)